Life is a school: Learning as a way of life - Prasad, VRK (New Delhi D. P. S. Publishing House, 2022)
Learning is not associated with any intelligence or an inborn skill. It is a trait bestowed by God almighty right from the days when one is in the womb of a mother who understands the needs of an unborn child.
Keywords: Life Learning; School Learning